2007
DOI: 10.1590/s0103-84782007000100029
|View full text |Cite
|
Sign up to set email alerts
|

Soroprevalência das infecções por parvovírus, adenovírus, coronavírus canino e pelo vírus da cinomose em cães de Santa Maria, Rio Grande do Sul, Brasil

Abstract: Seroprevalence of parvovirus, adenovirus, coronavirus and canine distemper virus infectionsin dogs of Santa Maria, Rio Grande do Sul, Brazil CPV in 68.7% (561/817), to CAV in 43% (353/817) RESUMO As infecções pelo vírus da cinomose (CDV), por parvovírus (CPV), adenovírus (CAV) e coronavírus (CCoV ABSTRACT Canine distemper virus (CDV), parvovirus (CPV), adenovirus (CAV) and coronavirus (CCoV) infections have been associated with significant morbidity and mortality among dogs worldwide yet very little is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
24

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 18 publications
2
13
0
24
Order By: Relevance
“…These results are similar to the ones reported in other studies (RIMMELZWAAN et al, 1991;TENNANT;JONES;GASKELL, 1993;BANDAI et al, 1999;NAYLOR et al, 2001;YEŞILBAĞ et al, 2004;DEZENGRINI;WEIBLEN, FLORES, 2007). The primary means of transmission is via exposure of susceptible hosts to virus shed in feces (CARMICHAEL; BINN, 1981).…”
Section: Resultssupporting
confidence: 91%
“…These results are similar to the ones reported in other studies (RIMMELZWAAN et al, 1991;TENNANT;JONES;GASKELL, 1993;BANDAI et al, 1999;NAYLOR et al, 2001;YEŞILBAĞ et al, 2004;DEZENGRINI;WEIBLEN, FLORES, 2007). The primary means of transmission is via exposure of susceptible hosts to virus shed in feces (CARMICHAEL; BINN, 1981).…”
Section: Resultssupporting
confidence: 91%
“…Epidemiological and/or prevalence studies realized in Brazil have demonstrated no difference relative to the possibility of infection occurring between male and female dogs (HEADLEY;GRAÇA 2000;BORBA et al, 2002;DEZENGRINI;WEIBLEN;FLORES, 2007;HASS et al, 2008;GUEDES et al, 2010). However, in some studies, proportionally more males relative to females were infected by CDV.…”
Section: Sexual Preference and Age-related Distribution Patternsmentioning
confidence: 99%
“…We proposed that new epidemiological studies should adopt one of the several age-related distribution patterns already existing, so that the new data can be easily compared. Nevertheless, most studies that have used several age-related groups (HEADLEY; GRAÇA, 2000;BORBA et al, 2002;DEZENGRINI;WEIBLEN;FLORES, 2007;SILVA et al, 2009;SONNE et al, 2009;GUEDES et al, 2010) provide a better evaluation of disease progression as age increases; while a few used only three groups (GOUVEIA; MAGALHÃES; RIBEIRO, 1987;SILVA et al, 2007). In those studies with several age-related groups, pups and young dogs were comparatively more frequently infected by CDV relative to older animals; this is in agreement with the fact that young pups are not fully protected by passive immunization, whereas young dogs might not have been fully vaccinated and hence apt to be infected by CDV (GREENE; APPEL, 2006), on being exposed to a clinically or subclinically infected dog.…”
Section: Sexual Preference and Age-related Distribution Patternsmentioning
confidence: 99%
“…Em alguns estudos de lesões crônicas (fibrose hepática) espontâneas do fígado em cães, observou-se, por imunoistoquímica, a presença de antígenos de CAV-1 (Rakich et al 1986). Alguns autores (Gocke et al 1970, Rakich et al 1986) sugerem, em razão disso, uma estudo que utilizou 817 amostras de soro de cães não-vacinados de Santa Maria, RS, 43% foram positivas para adenovírus canino (CAV) (Dezengrini et al 2007). Embora o estudo não diferencie claramente entre as infecções por CAV-1 (Hepatite infecciosa canina) e CAV-2 (doença respiratória), é provável que a infecção por CAV-1, em nosso meio, seja muito mais freqüente que a doença clínica.…”
Section: Discus Discus Discus Discus Discussão São São São Sãounclassified